An Unlikely Champion of Women’s Rights under Muslim Personal Law: Mawdūdi on the Anglo-Muhammadan Law - Shahbaz Cheema (Journal of Islamic Thought and Civilization, 2019)
Sayyid Abul Ala Mawdūdi was one of the most renowned Muslim scholars of the 20th century. In addition to his portrayal as a gender insensitive / women unfriendly scholar, he is regarded as one of the founding fathers of political Islam in the modern era for developing a comprehensive political theory of Islam. Mawdūdi was a prolific writer who wrote on a wide array of subjects, although there are some areas in which his contributions have never attracted the academic attention they deserve. With this background, this paper analyzes Mawdūdi’s book Huquq al-Zawjayn written during the British Rāj which has generated debates in the post-colonial legal landscape of Pakistan about some important issues related to women’s rights in marriage. Mawdūdi expressed unflinching disapproval of his contemporary Muslim scholars for their parasitic imitation of the rules of fiqh and their hesitation to have recourse to the divine sources, that is, Qur’ān and Sunnah for ushering solutions of then prevalent religious and social vices. Additionally, he criticized sternly the British Raj and the byproduct of its legal apparatus in the domain of family law, that is, the Anglo-Muhammadan law. Consequently, Mawdūdi presented a model for Muslim personal law inspired by and reconstructed from Qur’ānic verses and sayings of the Holy Prophet (SAW). Keywords: , , , ,